Rehabilitation following flexor tendon injury to the hand in African countries: a study protocol for a scoping review - Martin Marume; Susan De Klerk; Lee-Ann Jacobs-Nzuzi Khuabi (BMJ Open)
Methods and analysis The research will follow the scoping review methodological framework developed by Arksey and O’Malley (2005). The search strategy was developed and will be used to retrieve articles from eight databases. Further literature will be searched in the bibliography of the identified eligible articles. Grey literature will be searched in scientifically reliable websites, organisations and other sources. Articles will be reviewed by two independent researchers and opinion will be sought from a third reviewer when disagreement prevails on the inclusion quality of an article. All relevant articles that meet the criteria will be analysed using Weft QDA.Ethics and dissemination The scoping review paper will be discussed with local therapists. Thereafter, findings will be published in the year 2021 and sent to rehabilitation associations in respective African countries.